The complete mitochondrial genome of Neoris haraldi Schawerda (Lepidoptera: Saturniidae). Issue 2 (12th December 2017) - He, Yu-Ying; Wang, Xing; Chen, Liu-Sheng
Abstract: As an important insect pest on desert vegetation, Neoris haraldi has already brought great damage on Populus euphratica that was a key plant in the desert areas. Here, the complete mitochondrial genome (mitogenome) of N. haraldi has been sequenced with 15, 383 bp in length. The mitogenome has a base composition of A (39.4%), T (40.3%), C (12.4%), and G (7.9%), and consists of 13 protein-coding genes (PCGs), 22 transfer RNA (tRNA) genes, 2 ribosomal RNA (rRNA) genes, and an A + T-rich region. The phylogenetic relationships among the saturniid species were ( Neoris haraldi + (( Attacus atlas + ( Samia cynthia  + ( Samia canningi  +  Samia ricini ))) + (( Eriogyna pyretorum  +  Saturnia boisduvalii ) + (( Actias artemis  +  Actias selene ) + ( Antheraea assama + ( Antheraea frithi  + ( Antheraea pernyi    Antheraea yamamai ))))))), which was supported by a high bootstrap value of 100% and a posterior probability of 1.00.